2016
DOI: 10.3329/bjas.v45i2.29802
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of different organic acids on growth and nutrient digestibility of broiler

Abstract: An experiment was conducted to determine the effect of organic acids (acetic, butyric, citric and formic acids) on growth and nutrient digestibility of broilers. One hundred fifty (150) day old Hubbard chicks were used. There were five dietary treatments such viz Diet 1 as control contained no organic acid, diets 2, 3, 4, and 5 contained 0.25% acetic, butyric, citric and formic acids, respectively. Each treatment was replicated three times having 10 birds arranged in completely randomized design (CRD). Feed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…This change might be because of the expansion in the absorbability of supplements because of good gut conditions including diminished pH of digesta in various section, enhanced gut measure and morphometry, which represents expanded ingestion surface. These results are in concurrence with those detailed by Ndelekwute and Enyenihi (2017) who found that FCR was not significantly influenced for chicks by dietary PB supplementation during growth period.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This change might be because of the expansion in the absorbability of supplements because of good gut conditions including diminished pH of digesta in various section, enhanced gut measure and morphometry, which represents expanded ingestion surface. These results are in concurrence with those detailed by Ndelekwute and Enyenihi (2017) who found that FCR was not significantly influenced for chicks by dietary PB supplementation during growth period.…”
Section: Resultssupporting
confidence: 93%
“…1 and 2). These results are corrsistent with Ndelekwute and Enyenihi. (2017) who concluded that digestibility coefficients of nutrients was significantly (P≤0.01) improved by supplementing organic acids mixture to broiler diet as compared to the un-supplemented diet.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Feed grade enzymes, probiotics, prebiotics, yeast, spices and essential oils, have been reported to increase digestibility in monogastric animals. [9][10][11] Recently, Ndelekwute et al, 12 and Mohammed 13 reported that organic acids enhanced growth performance of broiler chicks. Earlier, Waldroup et al, 14 Patten & Waldroup 15 and Dibner 16 had emphasized the essentials of organic acids in nutrient utilization by broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Smulikowska, Czerwiński, Mieczkowska, & Jankowiak, 2008) illustrated increased nitrogen retention in the host supplemented with fat coated organic acids, because of their enhanced bioavailability in the distal digestive tract and the greater epithelial cell proliferation.In broiler chickens,Ndelekwute and Enyenihi (2017) reported that citric and ascorbic acids of lime juice improved digestibility of nutrient at 7 weeks of age of broiler chickens. Also,Ndelekwute et al (2018) found that digestion coefficients of protein, fibre and ether extract were significantly improved by addition of organic acids in drinking water (p < .05).…”
mentioning
confidence: 99%